2010
DOI: 10.1039/b9pp00012g
|View full text |Cite
|
Sign up to set email alerts
|

Is the action spectrum for the UV-induced production of previtamin D3 in human skin correct?

Abstract: The universally recognised action spectrum for the UV-induced conversion of 7-dehydrocholesterol to previtamin D(3) in human skin was published in 1982, and indicates a maximum at about 297 nm with essentially no production above 315 nm. This work represents a milestone in research on vitamin D, but limitations in the original data should be recognised. Various findings have arisen in recent years which cast doubts on the accuracy of the action spectrum and its application for spectral weighting in calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 50 publications
1
81
1
Order By: Relevance
“…(Brooke-Wavell et al, 2008, Macfarlane et al, 2005. Solar radiation is composed of 90-99% UVA and 1-10% UVB (Norval et al, 2010), when it reaches the highest point at noon at the equator (Thieden et. al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Brooke-Wavell et al, 2008, Macfarlane et al, 2005. Solar radiation is composed of 90-99% UVA and 1-10% UVB (Norval et al, 2010), when it reaches the highest point at noon at the equator (Thieden et. al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There is significant debate on the pre-vitamin D synthesis action spectrum (Norval et al 2009), however at the time of the data modelling this was the most appropriate weighting. This is the first time that a study has investigated the population level The cross-sectional analysis had several strengths and weaknesses.…”
Section: Natural Differences In Ambient Uvmentioning
confidence: 99%
“…However, since the regulative mechanism only works under irradiation of the spectrum of a black body emitter at the temperature of the sun, it is questionable to which extent the monochromatically derived action spectrum is capable to explain the photoequilibrium under the solar spectrum. At present, there is an ongoing dispute about the validity of several measured action spectra in the literature, 14 and a recent study has found that the action spectra vary between previously irradiated and unexposed skin sam-ples. 15 To date, the exact regulative mechanism of Vita photo production is still not well understood and no accurate quantitative predictions can be made.…”
Section: Introductionmentioning
confidence: 99%